(untitled) (Journal of the Bangladesh Agricultural University, 2020)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh to evaluate the effect of integration of herbicide with manual weeding on the performance of transplant aman rice cultivars during the period from July to November 2017. The experiment consisted of three transplant aman rice cultivars viz., BR11, BRRI dhan49 and Binadhan-7 with seven weeding treatments viz., no weeding (W0), two hand weedings at 15 and 30 DATs (W1), application of pre-emergence herbicide Pretilachlor (W2), application of early post emergence herbicide Acetachlor + Bensulfuron methyl (Pediplast) (W3), application of Pretilachlor followed by application of Pediplast (W4), application of Pretilachlor followed by one hand weeding at 30 DAT (W5) and application of Pediplast followed by one hand weeding at 30 DAT (W6). The experiment was laid out in a randomized complete block design with three replications. Weed density and dry weight were significantly affected by cultivars and weeding treatments. The maximum weed growth was noticed with the BR11 and the minimum with cultivar BRRI dhan49 at 20 DAT. The highest weed density and dry weight were noticed in no weeding treatment and the lowest value was found in application of Pediplast followed by one hand weeding at 30 DAT. Cultivar and weeding treatment exerted significant effect on yield and yield attributes of transplant aman rice. BRRI dhan49 produced the highest grain yield which was statistically identical with BR11 and Binadhan–7 produced the lowest grain yield. Application of Pediplast followed by one hand weeding at 30 DAT produced the highest grain yield which was statistically identical with other weeding treatments except no weeding. Rice cultivar BRRI dhan49 with the application of Pediplast followed by one hand weeding at 30 DAT produced numerically the highest grain yield. From the economic analysis, it is observed that the highest BCR was recorded from the application of Pediplast with BRRI dhan49. Therefore, application of early post emergence herbicide Pediplast with the cultivar BRRI dhan49 is effective and economic than the other weed control treatments in controlling weeds effectively and producing higher grain yield as well obtaining highest economic return. J Bangladesh Agril Univ 18(2): 340–346, 2020 https://doi.org/10.5455/JBAU.81118